Distribution, Feeding Habits, and Growth of Chub Mackerel, Scomber japonicus, Larvae During a High-Stock Period in the Northern Satsunan Area, Southern Japan - Kume, Gen; Shigemura, Taichi; Okanishi, Masahiro; Hirai, Junya; Shiozaki, Kazuhiro; Ichinomiya, Mutsuo; Komorita, Tomohiro; Habano, Akimasa; Makino, Fumihiro; Kobari, Toru (Frontiers in Marine Science, 2021)
To evaluate the importance of the northern Satsunan area in southern Japan as a spawning and nursery ground for chub mackerel (Scomber japonicus), we investigated their early life history characteristics (e.g., larval distribution, feeding habits, and growth) over five successive years. This area is considered the main habitat and spawning ground of the congeneric species S. australasicus. Using polymerase chain reaction-restriction fragment length polymorphism analysis, we first confirmed that S. japonicus larvae were abundant in the northern Satsunan area, potentially representing a major spawning and nursery ground in the Japanese Pacific coastal area. The number of recorded larvae started to increase in 2016, corresponding to the population dynamics of the Pacific stock of the species, which has shown increasing trends in recent years. Morphological and DNA metabarcoding analyses of gut contents and stable isotope analysis showed that, in addition to copepods, the larvae fed substantially on appendicularians. The trophic pathway involving appendicularians might support the feeding habits of S. japonicus, promoting its coexistence with other dominant species. Both the instantaneous growth rate and daily specific growth rate were comparable to those in the southern East China Sea, which is the main spawning and nursery ground of the species. Our data strongly suggest that the northern Satsunan area has favorable conditions for sustaining high larval population densities, even during phases with high population numbers. Our results provide insights for the fisheries management for S. japonicus in the Japanese Pacific coastal area, especially during high-stock periods.